Prophylactic use of an ultra-diluted complex on polymorphonuclear leukocyte function and respiratory scores of weaned Holstein calves immediately after grouping (Research, Society and Development, 2021)
The aim of the study was to evaluate the effect of an ultra-diluted complex supplementation as a prophylactic strategy on immunity, performance, and respiratory scores of weaned Holstein calves immediately after grouping. Thirty-six weaned Holstein female calves (80.4±1.3 days old; 105.6±10.4 kg) were allocated to 6 pens (n=6 per pen) in a completely randomized design experiment in a double-blind, placebo-controlled trial. During a 28 days period, animals received a total mixed ration and were enrolled into two different groups (n=18 per group): 1) Control (basal diet + calcium carbonate, top-dressed at 30 g/animal/d – ultra-diluted placebo vehicle), or 2) ultra-diluted complex (basal diet + TopVita™-Real H, top-dressed at 30 g/animal/d – Sulphur:10-60 + Viola tricolor:10-14 + Caladium seguinum:10-30 + Zincum oxydatum:10-30 + Phosphorus:10-60 + Cardus marianus:10-60 + Colibacillinum:10-30 + Podophyllum:10-30 + Vehicle: calcium carbonate; q.s. 1kg). Blood samples were collected from each heifer at enrollment and 28 days later to assess polymorphonuclear leukocyte (PMNL) function and blood cell count. Body weight was assessed at enrollment and 28 days later at the end of the study. Regarding respiratory-screening process, a calf scoring system modified for calves in group pens was used. There was no effect of prophylactic ultra-diluted treatment on PMNL, nor it affected lymphocytes count and its ratio. Besides, the ultra-diluted product did not affect body weight and ADG. Further, no effect was observed in respiratory scores throughout the study period. In conclusion, the ultra-diluted complex did not improve blood cells count and PMNL function, nor it had impact on the performance of weaned Holstein calves after grouping.